A review of stability analysis in islanded microgrids with photovoltaic integration - Ganeshan Viswanathan; Govindanayakanapalya Venkatagiriyappa Jayaramaiah (Institute of Advanced Engineering and Science, 2026)
Microgrids, emerging as a solution to meet rising energy demands and combat environmental issues, present unique challenges in stability analysis, especially when integrated with photovoltaic (PV) systems. This review explores the stability analysis of islanded microgrids with PV integration, addressing significant gaps in current understanding and methodologies. Firstly, the paper classifies microgrid stability into small signal, transient, and voltage stability, highlighting the distinct characteristics of each aspect. Subsequently, it provides an overview of stability analysis techniques, encompassing conventional, intelligent, and hybrid methodologies. The operational challenges faced by islanded microgrids are examined, along with effective control strategies to mitigate them. Moreover, the integration of photovoltaic systems into microgrids is scrutinized, including system configurations, stability impacts, and control methods. Finally, the paper discusses existing challenges and outlines future directions for advancing microgrid stability analysis. By explaining these critical aspects, this review underscores the necessity of enhancing stability analysis frameworks to ensure the robustness and reliability of islanded microgrids with PV integration in the evolving energy landscape.